2010
DOI: 10.21859/isv.4.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of H1 and H3 Influenza Virus Infection in Captive Birds in Tehran from November 2008 to February 2009

Abstract: Background and Aims: Influenza A virus infects birds and some mammalian including human. H1 and H3 subtypes are circulated in both human and birds' population. To determine the prevalence of the mentioned subtypes in birds, different captive bird species in Tehran zoo, and affiliated centers in Tehran were investigated for virus infection. Methods: In this study, Between November 2008 and February 2009, 76 cloacal swabs and serum samples were collected from 5 orders of Anseriformes, Galliformes, Columbiformes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…More than a decade ago, Fereidouni and colleagues detected H3 subtypes from aquatic birds, including a H3N8 from mallard (Fereidouni et al., 2010). Detection of H3 AIV from captive waterfowls in Tehran Zoo has been also reported (Heydarchi et al., 2010). However, in the current study we reported for the first time the isolation, whole genome sequence and characterisation of duck‐derived H3N2 AIV from Iran.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…More than a decade ago, Fereidouni and colleagues detected H3 subtypes from aquatic birds, including a H3N8 from mallard (Fereidouni et al., 2010). Detection of H3 AIV from captive waterfowls in Tehran Zoo has been also reported (Heydarchi et al., 2010). However, in the current study we reported for the first time the isolation, whole genome sequence and characterisation of duck‐derived H3N2 AIV from Iran.…”
Section: Discussionmentioning
confidence: 77%
“…Several reports on the AIV of low (Fereidouni et al., 2010; Ghalyanchi Langeroudi et al., 2013; Heydarchi et al., 2010; Mehrabadi et al., 2018; Nili & Asasi, 2003) and high pathogenicity (Ghafouri et al., 2019; Yegani et al., 2019) have been published from Iran. However, most of the works have studied the poultry, and therefore, little is known about the status and current subtypes of the AIV circulating in the Iranian domestic and wild waterfowls.…”
Section: Discussionmentioning
confidence: 99%
“…More than a decade ago, Fereidouni and colleagues detected H3 subtypes from aquatic birds, including a H3N8 from mallard (Fereidouni et al 2010). Detection of H3 AIV from captive waterfowls in Tehran Zoo has been also reported (Heydarchi et al 2010). However, in the current study we reported for the rst time the isolation, whole genome sequence and characterization of duckderived H3N2 AIV from Iran.…”
Section: Discussionmentioning
confidence: 83%
“…Several reports on the AIV of low (Nili and Asasi 2003;Fereidouni et al 2010;Heydarchi et al 2010;Ghalyanchi Langeroudi et al 2013;Mehrabadi et al 2018) and high pathogenicity (Yegani et al 2019;Ghafouri et al 2019) have been published from Iran. However, most of the works have studied the poultry, and therefore, little is known about the status and current subtypes of the AIV circulating in the Iranian domestic and wild waterfowls.…”
Section: Discussionmentioning
confidence: 99%